Informative Text Learning Through Processual Models to Improve Reading Comprehension Skills - Cengiz Erkan Toptaş; Gönül Şadoğlu (Papanda Publisher, 2022)
This study looked at how teaching informative text structures using a processual paradigm affected the reading comprehension abilities of fourth-graders. An experimental model with pre-test-post-test control groups was used in the research's design. The study's study group was made up of 62 fourth-graders who attended a public school in the Turkish province of Konya during the 2020–2021 academic year. For ten weeks, the experimental group taught the informative texts using the processual paradigm, whereas the control group used the Turkish course's curriculum. The Reading Comprehension Test and the Awareness Test of Informative Text Structures were utilized as data gathering instruments in the study. The study's data were analyzed using the following methods: mean, standard deviation, unpaired t-test, and one-way analysis of variance. The study's findings showed that the experimental group, which had been taught informative texts using a processual paradigm, had significantly lower reading comprehension levels and less understanding of the structures of those texts.